(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Since 2014, the Azienda ULSS 8 Berica of Vicenza has implemented a Diagnostic-Therapeutic Care Pathway (PDTA) for individuals affected by Amyotrophic Lateral Sclerosis (ALS), which is currently undergoing revision. From its inception, this pathway has been distinctive for being a PDTA not focused on the disease itself, but on the comprehensive care of the person affected by ALS and their family within the social context in which they live. It has several clear strengths, including: the presence of a dedicated case-manager nurse, available to address clinical, social, and care-related issues; the presence of a palliative care physician from the time of initial care; the ability to empower the patient by consistently placing them at the center of the care process; and effective monitoring of the pathway’s efficacy through monthly review meetings involving the entire team, as well as the use of process and outcome indicators to evaluate the realization of the various phases and the involvement of the anticipated professionals. The entire PDTA is centered on Shared Care Planning, not only in relation to what is refused, but also regarding what can be offered to the person to help them imagine and achieve a good quality of life. Particular attention is given to the practical application of the planning, with the goal of accompanying the person to the end of their journey, ensuring that what has been agreed upon is carried out. This paper aims to illustrate the history of this experience, highlighting its most significant aspects.